Menumbuhkan Literasi Artificial Intelligence (AI) untuk Siswa Sekolah Dasar melaluiPendidikan Science, Technology, Engineering, Art, and Mathematics (STEAM) - Amalia, Shofi Nur; Fatmawati, Malinda; Nuriana, Ervin (Universitas Nahdlatul Ulama Blitar, 2025)
The emergence of Artificial Intelligence (AI) is a representation of massive technological innovation in the world, including Indonesia. The convenience of AI covers all sectors, including the education sector. With all its convenience, AI also has a negative impact on its users. Therefore, literacy regarding AI needs to be carried out to anticipate all the negative impacts that could result. For example, AI users in the world of education are teachers and students. AI literacy needs to be applied to students with a STEAM approach. In this research, the DBR method was used with the research results of (1) literacy activities running smoothly, (2) knowing students' difficulties in AI literacy, (3) knowing new things that students had discovered.